Factors influencing the first home purchase decision of middle-income earners (M40) in Selangor, Malaysia - Paul Anthony Mariadas; Hussin Abdullah; Norehan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this study is to determine first home purchase decision among middle-income earners in Selangor, Malaysia. Factors such as finance, location, neighbourhood, and structural attributes were investigated. Data was collected using a probabilistic sampling method, particularly a stratified random sampling technique. The descriptive approach, correlation, and multiple regression analysis are used to analyse the data. This research found two factors that influenced the residential property purchase decision among middle-income earners in Selangor, Malaysia, which are financial and neighbourhood. By understanding the motivation behind purchasing their first home, middle-income earners would be able to gauge the factors that matter most before purchasing the property.